Menerapkan Latihan Literasi Numerasi Menggunakan Media Belajar Online di SD Negeri 060888 - Rivaldo Halomoan Sinaga; Mujahid Wahidin; Sri Wahyuni (Yayasan Literasi Sains Indonesia, 2023)
Teaching Campus is a learning platform that provides opportunities for students to learn outside the campus to train their ability to solve complex problems by becoming teacher partners to innovate in learning, development and creative, innovative learning models. Through this program, students will be more active in the field and hone their creativity for the sustainability and improvement of the quality of education. This journal will explain how the Teaching Campus Program is carried out. The locations in the Teaching Campus Program certainly vary. For this teaching campus is a program under the auspices of the University of North Sumatra or Mitra Usu which is located at UPT SD 060888 which is located at Jl. Darussalam, Babura, District. Medan Sunggal, Medan City, North Sumatra 20153. And in the introduction of this program, the Group Work method is also used. This group work method serves to find out the problems that exist among students, so that researchers can make a form of solution. The form of program completion carried out is Literacy and Numeracy Training in increasing students' interest in reading and also improving literacy skills in students and students.